Asociaciones y cooperativismo. (Revista Escenarios Sociojurídicos, 2025)
Cooperativism and associations in Colombia represent two complementary forms of organization in the solidarity economy, promoting collaboration, participatory democracy, and nonprofit community development, in addition to their impact on peacebuilding, social inclusion, and poverty reduction. With approximately 6.3 million members in 2023, cooperatives impact 38% of the population, promoting financial inclusion and formal employment especially in rural areas. In addition to the rise of associations across the country, with social, cultural, or economic goals, these models are linked to the SDGs (Sustainable Development Goals). This article analyzes the impact of cooperativism and associations, their legal framework, and proposes public policies to maximize their transformative potential, drawing on national and international experiences.